Risk Analysis in New Product Development Projects in the Technology Industry - Rachmiani, Rachmiani; Hussaen, Saddam; Sriwardiningsih, Enggal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
New product development projects in the technology industry are faced with various risks that can affect the success and sustainability of the project. This research aims to analyze the main risks that arise in the new product development process, including market, financial, regulatory, and technical risks. Through qualitative and quantitative approaches, this research identifies and evaluates the factors that influence each type of risk. The findings show that effective risk mitigation requires comprehensive planning, ongoing monitoring, and collaboration between various stakeholders. Practical recommendations are provided to assist project managers in managing risks and increasing the chances of project success.